(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: Postprandial somnolence or commonly referred to as food coma is generally experienced after the ingestion of afternoon meals. The performance of an individual gets affected after the ingestion of a heavy meal and this is more pertinent in a college setup where students have to attend a lecture right after the meal. The objective of this study was to assess the awareness of medical students about the factors responsible for postprandial somnolence, to identify the methods used to counteract it and to ascertain lecturers’ perception on responsiveness and participation of the students in a post lunch lecture. Methods: Total 330 students (first year to third year MBBS students) aged between 18-21 years and 40 lecturers teaching first and second year MBBS students were involved in this study. Two separate questionnaires (Part A: students’ perception, and B: lecturers’ perception) were prepared, peer-reviewed, validated and administered to the respective participants. All the responses were compiled and expressed in frequency percentage. Statistical analysis was performed using Statistical Package for Social Sciences, version 15.0 for a level of statistical significance of 5%. Pearson correlation was used to get the association between the variables. Results: About 55.75% students were aware about the role of serotonin and melatonin in drowsiness but 45.75% students did not know that food rich in tryptophan relaxes the brain and results in sleepiness. Students agree that heaviness of their meal might cause drowsiness and indigestion or bloating, which can also result in lethargy and can affect their performance. Majority of the lecturers opined that students disturb the harmony of the class and are less responsive and participative in post lunch break lectures. Conclusion: Thus, the present study provided scope for conducting awareness talks regarding the strategies to counteract postprandial somnolence among medical students which can help improve their concentration during post-lunch lectures. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.826-832